Analysis of the E-Government Initiative at Local Government Level in Bandung City, Indonesia - Tutik Rachmawati; Kusuma Dwi Fitriyanti (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
This research aims to analyze aspects affecting the implementation of electronic parking, a digital- based public services provision in parking. The concept of digital divide, workforce, regulation, and infrastructure were used to conduct the analysis. This study employed a qualitative research methodology with qualitative data collection techniques through interviews with two officers of the Parking Technical Implementation Unit (TIU) - the Department of Transportation Bandung City Government, 4 parking attendants, and 100 people as the roadside parking users. To enrich the data, observation and study documents were also conducted. The research used a descriptive analysis combined with simple descriptive quantitative data. It is evident from this study that four primary aspects hindered the implementation of the electronic-parking initiative. Those aspects are a large gap in the digital divide, low workforce quality and quantity, the absence of the proper regulations, and futile infrastructure. Adding to these four barriers, we also found other significant aspects: the investment that has not been strategically designed, the lack of leadership, and the low quality of education and marketing. All these three additional aspects also contribute to the failure in meeting the objective of the electronic parking initiative. This finding suggests that any new initiatives in public service provision, mainly using ICT, need to be well communicated and consulted with the implementing units. Furthermore, the initiative needs to be complemented with an acceptable set of policies to ensure its sustainability.